REVIEW: Călin-Horia Bârleanu, Benjy's Howl. Contributions on the typology of the idiot in literature - Alina Viorela Prelipcean (Association of Social and Educational Innovation, 2020)
With his innovative spirit, daring to the point of risk, including that of a self-mannerism, Călin-Horia Bârleanu, an academic from the University of Suceava tries, through his excellent study Strigătul lui Benjy. Contribuţii asupra tipologiei idiotului în literatură [Benjy's Howl. Contributions on the typology of the idiot in literature], an ontological decipherment, i.e. from the perspective of the "speculative theories about the ultimate essences or principles of all things" (MDA, 2010), which would premeditatedly avoid the "harmony of words, so deceptive and by which the trust, as a form of faith, has been emptied of any content"(p. 344), of "the typology of the patient with diminished mental capacity, real and equally projected on him" (p. 204), starting from and analyzing Faulkner's novel The Sound and the Fury, in which the typological character "is, among the resonant forms of the archetype, an entity as palpable as the fear of the dark or the obsessive «devouring jaws», because it represents and it is described by the American writer as a unique form of manifestation and communication"(p. 344), following "the unique typology of Benjy's projections" especially "through the psychoanalytic lens or the Jungian psychology"(p. 78).